2014
DOI: 10.1089/neu.2013.3087
|View full text |Cite
|
Sign up to set email alerts
|

Post-Traumatic Hypoxia Is Associated with Prolonged Cerebral Cytokine Production, Higher Serum Biomarker Levels, and Poor Outcome in Patients with Severe Traumatic Brain Injury

Abstract: Secondary hypoxia is a known contributor to adverse outcomes in patients with traumatic brain injury (TBI). Based on the evidence that hypoxia and TBI in isolation induce neuroinflammation, we investigated whether TBI combined with hypoxia enhances cerebral cytokine production. We also explored whether increased concentrations of injury biomarkers discriminate between hypoxic (Hx) and normoxic (Nx) patients, correlate to worse outcome, and depend on blood-brain barrier (BBB) dysfunction. Forty-two TBI patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(90 citation statements)
references
References 60 publications
3
83
0
2
Order By: Relevance
“…24,25 Post-traumatic hypoxia in patients with closed head trauma increases GM-CSF in the cerebrospinal fluid. 26 Whole body radiation that included brain induced increased synthesis of G-CSF that, although it contributes to BM recovery, 27 contributed to systemic immunosuppression (see section "Elevated G(M)-CSF is immunosuppressive in GB").…”
Section: Brain Tissue Injury Increases Brainsynthesized G(m)-csfmentioning
confidence: 99%
“…24,25 Post-traumatic hypoxia in patients with closed head trauma increases GM-CSF in the cerebrospinal fluid. 26 Whole body radiation that included brain induced increased synthesis of G-CSF that, although it contributes to BM recovery, 27 contributed to systemic immunosuppression (see section "Elevated G(M)-CSF is immunosuppressive in GB").…”
Section: Brain Tissue Injury Increases Brainsynthesized G(m)-csfmentioning
confidence: 99%
“…Adequate function of mitochondria is pivotal for the survival and activity of all brain cells, and even brief periods of oxygen or glucose deprivation could shut down brain functions within seconds, damaging neurons within minutes. 4 Abundant data from retrospective studies and prospective clinical trials have shown brain hypoxia to be an early predictor of adverse outcomes after TBI, [5][6][7] because efficient ATP production by the mitochondrial respiratory chain relies on continuous oxygen supply.…”
Section: Traumatic Brain Injury (Tbi)mentioning
confidence: 99%
“…In TBI the expression of S100 is upregulated and therefore could be responsible for hypocalcaemia by elevated calcium binding [19,27].…”
Section: Discussionmentioning
confidence: 99%